Quantitative Isotopomer Rates in Real‐Time Metabolism of Cells Determined by NMR Methods. (22nd July 2019) - Reed, Michelle A. C.; Roberts, Jennie; Gierth, Peter; Kupče, Ēriks; Günther, Ulrich L.
Abstract: Tracer‐based metabolism is becoming increasingly important for studying metabolic mechanisms in cells. NMR spectroscopy offers several approaches to measure label incorporation in metabolites, including 13 C‐ and 1 H‐detected spectra. The latter are generally more sensitive, but quantification depends on the proton–carbon 1 J CH coupling constant, which varies significantly between different metabolites. It is therefore not possible to have one experiment optimised for all metabolites, and quantification of 1 H‐edited spectra such as HSQCs requires precise knowledge of coupling constants. Increasing interest in tracer‐based and metabolic flux analysis requires robust analyses with reasonably small acquisition times. Herein, we compare 13 C‐filtered and 13 C‐edited methods for quantification and show the applicability of the methods for real‐time NMR spectroscopy of cancer‐cell metabolism, in which label incorporations are subject to constant flux. We find an approach using a double filter to be most suitable and sufficiently robust to reliably obtain 13 C incorporations from difference spectra. This is demonstrated for JJN3 multiple myeloma cells processing glucose over 24 h. The proposed method is equally well suited for calculating the level of label incorporation in labelled cell extracts in the context of metabolic flux analysis. Abstract : Filtering out the flux : The quantification of 1 H‐detected 13 C‐edited NMR spectra depends on a coupling constant that varies significantly between metabolites. Therefore, we have compared 13 C‐filtered and 13 C‐edited quantification methods and show their ability to robustly quantify 13 C‐label incorporation in real‐time for cancer‐cell metabolism, in which label incorporation is subject to constant flux.